2015
DOI: 10.1084/jem.20110575
|View full text |Cite
|
Sign up to set email alerts
|

CD68 acts as a major gateway for malaria sporozoite liver infection

Abstract: Cha et al. use a phage display library screen to identify a peptide, P39, that binds to CD68 on the surface of Kupffer cells to inhibit malaria sporozoite cell entry. Thus, P39 may represent a therapeutic strategy for malaria by limiting hepatic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 40 publications
3
71
0
Order By: Relevance
“…In addition, we used PMA‐activated THP‐1 macrophages as a surrogate for Kupffer cells. Human Kupffer cells are difficult to obtain, and we were unable to find enough cells to perform our studies; however, given that CD14 and CD68 are both biomarkers of human Kupffer cells and that our cells were both CD14 and CD68 positive, we used these cells instead; others have also used these cells to study Kupffer cell biology (50). Thus, it is likely that the findings from our studies are relevant and the mechanistic studies that relate palmitate to IGFBP‐3 suppression will provide potential future opportunities to translate these into novel approaches to limit systemic and hepatic inflammation in NAFLD and metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we used PMA‐activated THP‐1 macrophages as a surrogate for Kupffer cells. Human Kupffer cells are difficult to obtain, and we were unable to find enough cells to perform our studies; however, given that CD14 and CD68 are both biomarkers of human Kupffer cells and that our cells were both CD14 and CD68 positive, we used these cells instead; others have also used these cells to study Kupffer cell biology (50). Thus, it is likely that the findings from our studies are relevant and the mechanistic studies that relate palmitate to IGFBP‐3 suppression will provide potential future opportunities to translate these into novel approaches to limit systemic and hepatic inflammation in NAFLD and metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…A study performed by Cha et al 62 showed that CD68 can serve as a receptor for binding malaria sporozoite, which promotes subsequent infection of resident hepatic macrophages. Data obtained by Song et al 54 indicate a lack of any involvement of macrosialin/CD68 in inflammatory responses to bacterial/viral pathogens and innate/ humoral immunity.…”
Section: Cd68: a Role In Inflammation And Immunitymentioning
confidence: 99%
“…In this manner, the tetraspanin CD81, a surface molecule on hepatocytes and one of the main receptors for HCV , was identified as a crucial host factor for hepatocyte invasion of both, P. falciparum and P. yoelii sporozoites . Similarly, Cha and coworkers determined a critical role of host CD68 as a putative receptor for sporozoite invasion and traversal of Kupffer cells . A final relevant example is the host protein L‐FABP (liver‐fatty acid‐binding protein) that was found to specifically interact with the PV membrane‐resident protein, UIS3 (up‐regulated in sporozoites 3, ) within the infected hepatocyte, and which is presumably required for fatty acid uptake into the parasite .…”
Section: Wanted Ex or In Vivo—host Factors Involved In Intrahepatic Pmentioning
confidence: 99%